2018
DOI: 10.1002/14651858.cd010558.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies for treatment-resistant depression in adults

Abstract: Background Antidepressants are a first-line treatment for adults with moderate to severe major depression. However, many people prescribed antidepressants for depression don't respond fully to such medication, and little evidence is available to inform the most appropriate 'next step' treatment for such patients, who may be referred to as having treatment-resistant depression (TRD). National Institute for 1. Any psychological therapy versus antidepressant treatment alone, or another psychological therapy. 2. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 139 publications
2
81
1
4
Order By: Relevance
“…Conventional meta‐analyses of trials directly comparing psychotherapies and pharmacotherapies have suggested that, as classes of treatments, they have comparable effects, with no or only minor differences, although there may be some influence of placebo effects, sponsorship bias, and possibly the superiority of some medications over others. Other pairwise meta‐analyses have found that the combination of psychotherapy and pharmacotherapy may be more effective than either of these alone, although the evidence is not conclusive. Moreover, some studies suggest that the two monotherapies result in differential effects over long‐term follow‐ups, with psychotherapy having enduring effects on depression when pharmacotherapy is discontinued.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional meta‐analyses of trials directly comparing psychotherapies and pharmacotherapies have suggested that, as classes of treatments, they have comparable effects, with no or only minor differences, although there may be some influence of placebo effects, sponsorship bias, and possibly the superiority of some medications over others. Other pairwise meta‐analyses have found that the combination of psychotherapy and pharmacotherapy may be more effective than either of these alone, although the evidence is not conclusive. Moreover, some studies suggest that the two monotherapies result in differential effects over long‐term follow‐ups, with psychotherapy having enduring effects on depression when pharmacotherapy is discontinued.…”
mentioning
confidence: 99%
“…Several issues regarding the differential effects of combined treatment, psychotherapies and pharmacotherapies remain unsolved. Existing meta‐analyses have compared only two interventions at a time: psychotherapy vs. pharmacotherapy, combined treatment vs. psychotherapy, and combined treatment vs. pharmacotherapy. To get a better understanding of the relative effectiveness of these treatments, it is necessary to combine direct and indirect evidence from all clinical trials.…”
mentioning
confidence: 99%
“…Fortunately, interventions targeting these psychological comorbidities are well-established for the general population (31,146). However, psychological care guidelines are less well developed for patients with chronic lung disease (147).…”
Section: Treatment Approaches For Anxiety and Depression In Patients mentioning
confidence: 99%
“…Psychological therapies used in this population have mainly been those that use elements of cognitive and/or behavioural approaches (146), like relaxation therapy (149) and cognitive behavioural therapy (CBT) (150). Other additional therapies for chronic lung diseases have been linked with improvement in anxiety and depression, such as self-management strategies (31) and pulmonary rehabilitation (38)(39)(40).…”
Section: Treatment Approaches For Anxiety and Depression In Patients mentioning
confidence: 99%
See 1 more Smart Citation